Self-supporting diamond polycrystal material as well as preparation method and application thereof
By sintering 50 μm to 900 μm diamond particles under high temperature and high pressure and using cobalt as a sintering additive, the problem of insufficient thermal conductivity of existing ceramic substrate thermal conductivity is solved, and the preparation of a self-supporting diamond polycrystalline material with high thermal conductivity is realized. Suitable for heat dissipation applications of high-power electronic components.
Patent Information
- Application Number
- CN202411581921.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-14
AI Technical Summary
The existing ceramic substrate thermal conductivity has low thermal conductivity and cannot meet the heat dissipation needs of high-power electronic components. Moreover, the preparation method of diamond polycrystalline has problems with high cost and technical threshold.
The new diamond grains formed by secondary growth and saturated solution of carbon in metal are used to improve the thermal conductivity of the material.
A self-supported diamond polycrystalline material with a high thermal conductivity of 1100W/(m·K) is achieved, which is low in cost and suitable for industrial promotion, and solves the problem of insufficient thermal conductivity of traditional thermal conductivity.
Smart Images

Figure CN119433267A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of non-metallic materials, and more specifically to a self-supporting diamond polycrystalline material and a preparation method and application thereof. Background Art
[0002] At present, the heat dissipation materials of high-power electronic components are mainly various ceramic substrates, such as alumina, aluminum nitride, silicon nitride, etc., but the thermal conductivity of these thermal conductive materials is relatively low, at about 100W / (m·K), and the highest thermal conductive ceramic material is only 500W / (m·K). Faced with the continuous improvement of the power density of electronic components, traditional ceramic materials can no longer meet this demand.
[0003] Diamond has a strong heat transfer capability and is the material with the highest thermal conductivity in nature. Its thermal conductivity can reach 2000W / (m·K) at room temperature, and its thermal expansion coefficient is about (0.86±0.1)*10 -5 / K, and is insulating at room temperature. In addition, diamond also has excellent mechanical, acoustic, optical, electrical and chemical properties, which give it a clear advantage in the heat dissipation problem of high-power optoelectronic devices, which also shows that diamond has great application potential in the field of heat dissipation. Diamond polycrystal is a process that uses diamond as a skeleton material and metal catalyst cobalt as a catalyst. After the original diamond grain surface is graphitized under high pressure and high temperature conditions, diamond secondary nucleation growth is achieved to achieve bonding between diamond grains and realize the preparation of large-sized diamond polycrystalline materials.
[0004] By using fine-grained sintered diamond polycrystals, a finer cutting edge can be achieved on the cutting edge of the tool or tool; and the structure of fine-grained diamond polycrystals is denser than that of coarse-grained structures. Therefore, diamond polycrystals are used in abrasives and grinding tools, and more fine-grained diamonds are used for preparation. At present, diamond polycrystals are generally made of diamonds with a particle size of less than 20μm and sintering aids. Because of their excellent hardness and good wear resistance, they are widely used in tools, geological drill bits, diamond processing and machining tools. Because of the use of fine-grained diamonds and a large amount of metal sintering aids, the thermal conductivity is poor, only 50W / (m·K)~80W / (m·K). At present, the thermal conductivity of diamond polycrystals synthesized by chemical vapor deposition reaches 1500W / (m·K)~2000W / (m·K), but it has the problems of high synthesis technology threshold, long cycle, low production capacity and high price. Summary of the invention
[0005] In view of the above problems, the present invention provides a self-supporting diamond polycrystalline material and a preparation method and application thereof. The present invention uses 50μm to 900μm diamond particles as raw materials to prepare the self-supporting diamond polycrystalline material under high temperature and high pressure conditions. The method of the present invention has the advantages of simplicity, low cost, and easy large-scale growth.
[0006] The first object of the present invention is to provide a method for preparing a self-supporting diamond polycrystalline material, comprising the following steps:
[0007] Using cobalt as a binder, diamond particles of 50 μm to 900 μm are sintered at 1390° C. to 1420° C. and 5.7 GPa to 6.0 GPa. During the sintering process, secondary growth occurs between the diamond particles. After sintering, impurities are removed to obtain a self-supporting diamond polycrystalline material.
[0008] For example, the particle size of the diamond particles is 50μm, 100μm, 200μm, 300μm, 400μm, 500μm, 600μm, 700μm, 800μm, 900μm, etc., the sintering temperature is 1390℃, 1400℃, 1410℃, 1420℃, etc., and the sintering pressure is 5.7GPa, 5.8GPa, 5.9GPa, 6.0GPa, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0009] In a preferred embodiment of the present invention, the particle size of the diamond particles is 200μm to 900μm. For example, the particle size of the diamond particles is 200μm, 300μm, 400μm, 500μm, 600μm, 700μm, 800μm, 900μm, etc., but is not limited to the listed values. Other unlisted values within the above numerical range are also applicable.
[0010] In a preferred embodiment of the present invention, the particle size of the diamond particles is 500 μm.
[0011] In a preferred embodiment of the present invention, the mass ratio of diamond particles to cobalt is 1:0.25-0.3. For example, the mass ratio of diamond particles to cobalt is 1:0.25, 1:0.26, 1:0.27, 1:0.28, 1:0.29, 1:0.3, etc., but is not limited to the listed values. Other values not listed within the above numerical range are also applicable.
[0012] In a preferred embodiment of the present invention, the sintering method is: when the pressure is applied to 3.5 GPa to 3.8 GPa, heating is started to 1390°C to 1420°C, and the pressure is increased to 5.7 GPa to 6.0 GPa for sintering. For example, the pressure is applied to 3.5 GPa, 3.6 GPa, 3.7 GPa, 3.8 GPa, etc., but it is not limited to the listed values, and other values not listed in the above numerical range are also applicable.
[0013] In a preferred embodiment of the present invention, the sintering time is 10 min-60 min, for example, the sintering time is 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0014] In a preferred embodiment of the present invention, the impurity removal method is: placing the sintered sample in nitric acid to remove excess cobalt, and then placing it in a mixed acid and heating it at 230°C to 250°C to remove residual metal and graphite. For example, the heating temperature is 230°C, 235°C, 240°C, 245°C, 250°C, etc., but is not limited to the listed values, and other values not listed in the above numerical range are also applicable.
[0015] In a preferred embodiment of the present invention, the heating time is 60 hours to 62 hours. For example, the heating time is 60 hours, 60.5 hours, 61 hours, 61.5 hours, 62 hours, etc., but it is not limited to the listed values, and other values not listed in the above value range are also applicable.
[0016] The second object of the present invention is to provide a self-supporting diamond polycrystalline material prepared by the above preparation method.
[0017] The third object of the present invention is to provide the use of the self-supporting diamond polycrystalline material in the preparation of thermal conductive materials.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The present invention adopts a high temperature and high pressure method to prepare diamond polycrystals. Compared with the preparation method of chemical vapor deposition, the preparation method of the present invention has the advantages of being simple, low cost and easy to grow on a large scale. The present invention uses low-cost abrasive grade diamond, the particle size of the diamond is 50μm to 900μm, and metal cobalt is used as a sintering aid. Due to the large particle size of coarse-grained diamond, it can be more easily connected and accumulated in the sintered body to form a relatively continuous heat conduction channel. During the sintering process, some diamond particles in the diamond polycrystal will dissolve, and carbon atoms will interact with the surrounding metal binder to form a saturated solution of carbon in the metal. As the dissolution process proceeds, when the carbon atom concentration in the local area exceeds the saturation concentration, the carbon atoms will re-precipitate at other positions in the diamond polycrystal to form new diamond grains, realizing secondary growth polymerization between coarse-grained diamond grains, and forming a heat conduction path of the pure diamond contact end, and its thermal conductivity is up to 1100W / (m·K). Large-sized, high-thermal-conductivity, electrically-insulating diamond polycrystalline materials are prepared through high temperature and high pressure. This material is low-cost and suitable for industrial promotion and use, solving the current demand for low-cost heat dissipation materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The following is an assembly diagram.
[0021] Figure 2 Flow chart for sample preparation.
[0022] Figure 3 This is a physical picture of the diamond polycrystalline wafer prepared in Example 8.
[0023] Figure 4 These are scanning electron microscope images of the diamond polycrystals prepared in Example 8, wherein Figure a is a scanning electron microscope image of the sample surface, Figure b is a scanning electron microscope image of the sample after polishing, and Figure c is a scanning electron microscope image of the pores between the particles.
[0024] Figure 5 This is a scanning electron microscope image of the pores between the diamond polycrystalline particles prepared in Example 3.
[0025] Figure numerals: 1 - conductive steel ring; 2 - MgO / Al2O3 ring; 3 - NaCl / Zr2O tube; 4 - sample; 5 - metal sheet + carbon sheet; 6 - pyrophyllite; 7 - graphite tube; 8 - MgO / ZrO2 column; 9 - dolomite. DETAILED DESCRIPTION
[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] As shown in the background technology, in the prior art, when preparing diamond polycrystals, fine-grained diamonds and a large amount of metal sintering aids are used, so the thermal conductivity is poor, only 50W / (m·K) to 80W / (m·K). Based on this, the present invention provides a method for preparing a self-supporting diamond polycrystal material, and the specific technical scheme is as follows:
[0028] Using cobalt as a binder, diamond particles of 50 μm to 900 μm are sintered at 1390° C. to 1420° C. and 5.7 GPa to 6.0 GPa. During the sintering process, secondary growth grains exist between the diamond particles. After sintering, impurities are removed to obtain a self-supporting diamond polycrystalline material.
[0029] In order to improve the thermal conductivity of diamond polycrystals and develop their applications in the field of thermal management, the present invention introduces coarse-grained diamond single crystals into the traditional diamond polycrystal system for the first time, and uses metal cobalt as a sintering aid to achieve secondary growth polymerization between coarse-grained diamond grains, forming a heat conduction path at the contact end of pure diamond, and its thermal conductivity reaches up to 1100W / (m·K). In the preparation process of the present invention, the high temperature of 1390℃~1420℃ can make the diamond surface of the diamond voids graphitized, and the metal infiltrates into the diamond particle voids. The reason for the pressure of 5.7GPa~6.0GPa is that when the pressure is higher than the phase equilibrium pressure of diamond and graphite, overpressure is generated, and carbon is precipitated in the form of diamond to fill the voids, thereby improving the thermal conductivity of the sample. For the relatively coarse-grained diamond in the present invention, the gap is large, and a higher pressure is required to compress the gap, but the pressure cannot be too high to avoid particle rupture. In the present invention, relatively fine-grained diamond has a large specific surface area, and requires higher energy to promote sintering. Usually, the temperature is set higher, and the gap between small-grained particles is small, requiring higher pressure to promote close bonding. In actual sintering, the specific sintering conditions need to be determined based on the microstructure and physical properties of the sintered body.
[0030] Compared with diamond polycrystals synthesized by chemical vapor deposition, the preparation method of the present invention has the advantages of simplicity, low cost, and easy large-scale growth.
[0031] Smaller diamond particles mean more interfaces, that is, more interface thermal resistance, which is not conducive to improving thermal conductivity. Further, the present invention selects diamond particles with a particle size of 200 μm to 900 μm, and further, the particle size of the diamond particles is 500 μm.
[0032] Cobalt is used as a catalyst. The increase in the amount of cobalt added may affect the crystallization quality and impurity content of diamond polycrystals to a certain extent, resulting in a decrease in thermal conductivity. If the amount of cobalt added is too little, it may affect the diamond nucleation and growth process, making the crystallization integrity of the polycrystals less than ideal, which may also reduce thermal conductivity. Further, the mass ratio of diamond particles to cobalt is 1:0.25-0.3.
[0033] The sintering method is: when the pressure is applied to 3.5 GPa to 3.8 GPa, the temperature is heated to 1390°C to 1420°C, and the pressure is increased to 5.7 GPa to 6.0 GPa for sintering. It is understood that applying the pressure to 3.5 GPa to 3.8 GPa first and then increasing the temperature can prevent the diamond particles from graphitizing and avoid reducing the thermal conductivity due to the graphitization of diamond.
[0034] It should be noted that the process curve of the six-sided hammer equipment generally follows the process of increasing pressure first and then heating. During the process of increasing pressure, the atomic distance inside the material will be compressed, which is conducive to the interaction and reaction between atoms when the temperature rises later. In addition, the increase in pressure can limit the volume expansion of the material and reduce thermal stress and thermal deformation. In addition, applying high temperature first will cause the block to explode and damage the six-sided hammer. On the other hand, it may cause phase change, decomposition or other adverse physical and chemical reactions in the material.
[0035] A long sintering time will allow the diamond grains to be fully precipitated and reduce the air thermal resistance. Furthermore, the sintering time is 10min-60min.
[0036] The present invention is based on Figure 1 The assembly schematic diagram shown in the figure assembles a conductive steel ring 1, a MgO / Al2O3 ring 2, a NaCl / Zr2O tube 3, a sample 4, a metal sheet + carbon sheet 5, pyrophyllite 6, a graphite tube 7, a MgO / ZrO2 column 8, and dolomite 9. The metal sheets include iron, copper, and molybdenum. During assembly, the metal sheets and carbon sheets are placed in the order of 2 iron sheets, 1 copper sheet, 1 molybdenum sheet, and 1 carbon sheet. The carbon sheet is closest to the middle of the block. Then, the sheet is placed in a six-sided top press for high-temperature and high-pressure sintering. After sintering, the sample is first placed in dilute nitric acid to remove excess metal cobalt on the surface. Then, the diamond polycrystalline block is placed in a mixed acid (nitric acid and sulfuric acid) and heated for a long time to remove residual metal and graphite. The prepared sample is in the form of a sheet. After multiple ultrasonic treatments with anhydrous ethanol and deionized water, a black surface glossy, high thermal conductivity, and insulating diamond polycrystalline block can be obtained. The preparation flow chart is shown in the figure below. Figure 2 shown.
[0037] It should be noted that the samples refer to diamond particles and cobalt flakes, and the NaCl / Zr2O column is made by mixing NaCl and Zr2O powders in a mass ratio of 2:1 and grinding them for 20 minutes. The mold is pressed into a 15mm high tube at a pressure of 5Mpa and then baked at 400℃ for 3h.
[0038] MgO / Al2O3 rings are made by mixing MgO and Al2O3 powders in a mass ratio of 1:1 and grinding them for 20 minutes. The mold is pressed into a 4mm high ring at a pressure of 5Mpa and then baked at 970℃ for 3h.
[0039] MgO / ZrO2 column is made by mixing MgO and ZrO2 powders in a mass ratio of 4:1 and grinding them for 20 minutes. The mold was pressed into a column with a height of 8 mm under a pressure of 5 MPa and then baked at 970°C for 3 hours.
[0040] It should be noted that the assembly components described in the following embodiments are collectively referred to as the conductive steel ring 1, MgO / Al2O3 ring 2, NaCl / Zr2O tube 3, sample 4, metal sheet + carbon sheet 5, pyrophyllite 6, graphite tube 7, MgO / ZrO2 column 8, and dolomite 9. The mixed acid (nitric acid and sulfuric acid) used in the present invention is a mixture of 18.4 mol / L concentrated sulfuric acid and 14 mol / L concentrated nitric acid in a volume ratio of 1:3.
[0041] Example 1
[0042] 50μm diamond particles were acid-washed and rinsed with deionized water and stored in a drying oven; the dried diamond particles were placed in the assembly, cobalt sheets were placed on the top and bottom surfaces of the diamond particles, the mass ratio of diamond particles to cobalt sheets was 1:0.25, and the assembly components were isolated with a boron nitride cup, that is, the sample was placed in a boron nitride cup. After assembly, it was placed in a six-sided top press device, and high-temperature and high-pressure sintering was started in an air environment. The sintering pressure was set to 5.7GPa, and the pressure was applied at a rate of 7MPa / min to 3.5GPa by a six-sided hammer, and then heated to 1390℃ at a rate of 200℃ / min, and then the pressure was raised to 5.7GPa, and the temperature was kept for 30min. The heating was stopped first and then the pressure was released. After the end, the diamond polycrystalline block was taken out. The sample was first placed in 6 mol / L dilute nitric acid at room temperature for 12 hours to remove the excess metal cobalt on the surface, and then the diamond polycrystalline block was placed in a mixed acid (nitric acid and sulfuric acid) and heated at about 250°C for 60 hours to remove the residual metal and graphite. The sintered sample was in the form of a sheet, and after multiple ultrasonic treatments in anhydrous ethanol and deionized water, a black surface, shiny and insulating DD-bonded diamond polycrystalline block was obtained.
[0043] The test shows that its thermal conductivity reaches 544W / (m·K).
[0044] Example 2
[0045] 100μm diamond particles were acid-washed and rinsed with deionized water and stored in a drying oven; the dried diamond particles were placed in the assembly, cobalt sheets were placed on the top and bottom surfaces of the diamond particles, the mass ratio of diamond particles to cobalt sheets was 1:0.25, and the assembly components were isolated with a boron nitride cup, that is, the sample was placed in the boron nitride cup. After assembly, it was placed in a six-sided top press device, and high-temperature and high-pressure sintering began in an air environment. The sintering pressure was set to 5.7GPa, and the six-sided hammer began to apply pressure at a rate of 7MPa / min to 3.5GPa, and then began to heat to 1390℃ at a rate of 200℃ / min, and then the pressure was raised to 5.7GPa, and the temperature was kept for 30min. The heating was stopped first and then the pressure was released. After the end, the diamond polycrystalline block was taken out. The sample was first placed in 6 mol / L dilute nitric acid at room temperature for 12 hours to remove the excess metal cobalt on the surface, and then the diamond polycrystalline block was placed in a mixed acid (nitric acid and sulfuric acid) and heated at about 250°C for 60 hours to remove the residual metal and graphite. The sintered sample was in the form of a sheet, and after multiple ultrasonic treatments in anhydrous ethanol and deionized water, a black surface, shiny and insulating DD-bonded diamond polycrystalline block was obtained.
[0046] The test shows that its thermal conductivity reaches 700W / (m·K).
[0047] Example 3
[0048] 200μm diamond particles were acid-washed and rinsed with deionized water and stored in a drying oven; the dried diamond particles were placed in the assembly, cobalt sheets were placed on the top and bottom surfaces of the diamond particles, the mass ratio of diamond particles to cobalt sheets was 1:0.25, and the assembly components were isolated with a boron nitride cup, that is, the sample was placed in a boron nitride cup. After assembly, it was placed in a six-sided top press device, and high-temperature and high-pressure sintering began in an air environment. The sintering pressure was set to 5.7GPa, and the six-sided hammer began to apply pressure at a rate of 7MPa / min to 3.5GPa, and then began to heat to 1390℃ at a rate of 200℃ / min, and then the pressure was raised to 5.7GPa, and the temperature was kept for 30min. The heating was stopped first and then the pressure was released. After the end, the diamond polycrystalline block was taken out. The sample was first placed in 6 mol / L dilute nitric acid at room temperature for 12 hours to remove the excess metal cobalt on the surface, and then the diamond polycrystalline block was placed in a mixed acid (nitric acid and sulfuric acid) and heated at about 250°C for 60 hours to remove the residual metal and graphite. The sintered sample was in the form of a sheet, and after multiple ultrasonic treatments in anhydrous ethanol and deionized water, a black surface, shiny and insulating DD-bonded diamond polycrystalline block was obtained.
[0049] The test shows that its thermal conductivity reaches 850W / (m·K).
[0050] Figure 5This is a scanning electron microscope image of the magnified pores in Example 3. Compared with Example 8, when using diamond with a smaller particle size as the raw material, the secondary grain size formed may be smaller and have more grain boundaries.
[0051] Example 4
[0052] 300μm diamond particles were acid-washed and rinsed with deionized water and stored in a drying oven; the dried diamond particles were placed in the assembly, cobalt sheets were placed on the top and bottom surfaces of the diamond particles, the mass ratio of diamond particles to cobalt sheets was 1:0.25, and the assembly components were isolated with a boron nitride cup, that is, the sample was placed in a boron nitride cup. After assembly, it was placed in a six-sided top press device, and high-temperature and high-pressure sintering began in an air environment. The sintering pressure was set to 5.7GPa, and the six-sided hammer began to apply pressure at a rate of 7MPa / min to 3.5GPa, and then began to heat to 1390℃ at a rate of 200℃ / min, and then the pressure was raised to 5.7GPa, and the temperature was kept for 30min. The heating was stopped first and then the pressure was released. After the end, the diamond polycrystalline block was taken out. The sample was first placed in 6 mol / L dilute nitric acid at room temperature for 12 hours to remove the excess metal cobalt on the surface, and then the diamond polycrystalline block was placed in a mixed acid (nitric acid and sulfuric acid) and heated at about 250°C for 60 hours to remove the residual metal and graphite. The sintered sample was in the form of a sheet, and after multiple ultrasonic treatments in anhydrous ethanol and deionized water, a black surface, shiny and insulating DD-bonded diamond polycrystalline block was obtained.
[0053] The test shows that its thermal conductivity reaches 880W / (m·K).
[0054] Example 5
[0055] 500μm diamond particles were acid-washed and rinsed with deionized water and stored in a drying oven; the dried diamond particles were placed in the assembly, cobalt sheets were placed on the top and bottom surfaces of the diamond particles, the mass ratio of diamond particles to cobalt sheets was 1:0.25, and the assembly components were isolated with a boron nitride cup, that is, the sample was placed in a boron nitride cup. After assembly, it was placed in a six-sided top press device, and high-temperature and high-pressure sintering began in an air environment. The sintering pressure was set to 5.7GPa, and the six-sided hammer began to apply pressure at a rate of 7MPa / min to 3.5GPa, and then began to heat to 1390℃ at a rate of 200℃ / min, and then the pressure was raised to 5.7GPa, and the temperature was kept for 30min. The heating was stopped first and then the pressure was released. After the end, the diamond polycrystalline block was taken out. The sample was first placed in 6 mol / L dilute nitric acid at room temperature for 12 hours to remove the excess metal cobalt on the surface, and then the diamond polycrystalline block was placed in a mixed acid (nitric acid and sulfuric acid) and heated at about 250°C for 60 hours to remove the residual metal and graphite. The sintered sample was in the form of a sheet, and after multiple ultrasonic treatments in anhydrous ethanol and deionized water, a black surface, shiny and insulating DD-bonded diamond polycrystalline block was obtained.
[0056] The test shows that its thermal conductivity reaches 945W / (m·K).
[0057] Example 6
[0058] 900μm diamond particles were acid-washed and rinsed with deionized water and stored in a drying oven; the dried diamond particles were placed in the assembly, cobalt sheets were placed on the top and bottom surfaces of the diamond particles, the mass ratio of diamond particles to cobalt sheets was 1:0.25, and the assembly components were isolated with a boron nitride cup, that is, the sample was placed in a boron nitride cup. After assembly, it was placed in a six-sided top press device, and high-temperature and high-pressure sintering was started in an air environment. The sintering pressure was set to 5.7GPa, and the six-sided hammer was used to apply pressure at a rate of 7MPa / min to 3.5GPa, and then heated to 1390℃ at a rate of 200℃ / min, and then the pressure was raised to 5.7GPa, and the temperature was kept for 30min. The heating was stopped first and then the pressure was released. After the end, the diamond polycrystalline block was taken out. The sample was first placed in 6 mol / L dilute nitric acid at room temperature for 12 hours to remove the excess metal cobalt on the surface, and then the diamond polycrystalline block was placed in a mixed acid (nitric acid and sulfuric acid) and heated at about 250°C for 60 hours to remove the residual metal and graphite. The sintered sample was in the form of a sheet, and after multiple ultrasonic treatments in anhydrous ethanol and deionized water, a black surface, shiny and insulating DD-bonded diamond polycrystalline block was obtained.
[0059] The test shows that its thermal conductivity reaches 830W / (m·K).
[0060] Example 7
[0061] 200μm diamond particles were acid-washed and rinsed with deionized water and stored in a drying oven; the dried diamond particles were placed in the assembly, cobalt sheets were placed on the top and bottom surfaces of the diamond particles, the mass ratio of diamond particles to cobalt sheets was 1:0.25, and the assembly components were isolated with a boron nitride cup, that is, the sample was placed in the boron nitride cup. After assembly, it was placed in a six-sided top press equipment, and high-temperature and high-pressure sintering began in an air environment. The sintering pressure was set to 5.7GPa, and the six-sided hammer began to apply pressure at a rate of 7MPa / min to 3.5GPa, and then began to heat to 1390℃ at a rate of 200℃ / min, and then the pressure was raised to 5.7GPa, and the temperature was kept for 60min. The heating was stopped first and then the pressure was released. After the end, the diamond polycrystalline block was taken out. The sample was first placed in 6 mol / L dilute nitric acid at room temperature for 12 hours to remove the excess metal cobalt on the surface, and then the diamond polycrystalline block was placed in a mixed acid (nitric acid and sulfuric acid) and heated at about 250°C for 60 hours to remove the residual metal and graphite. The sintered sample was in the form of a sheet, and after multiple ultrasonic treatments in anhydrous ethanol and deionized water, a black surface, shiny and insulating DD-bonded diamond polycrystalline block was obtained.
[0062] The test shows that its thermal conductivity reaches 850W / (m·K).
[0063] Example 8
[0064] 500μm diamond particles were acid-washed and rinsed with deionized water and stored in a drying oven; the dried diamond particles were placed in the assembly, cobalt sheets were placed on the top and bottom surfaces of the diamond particles, the mass ratio of diamond particles to cobalt sheets was 1:0.25, and the assembly components were isolated with a boron nitride cup, that is, the sample was placed in a boron nitride cup. After assembly, it was placed in a six-sided top press device, and high-temperature and high-pressure sintering began in an air environment. The sintering pressure was set to 5.7GPa, and the six-sided hammer began to apply pressure at a rate of 7MPa / min to 3.5GPa, and then began to heat to 1390℃ at a rate of 200℃ / min, and then the pressure was raised to 5.7GPa, and the temperature was kept for 60min. The heating was stopped first and then the pressure was released. After the end, the diamond polycrystalline block was taken out. The sample was first placed in 6 mol / L dilute nitric acid at room temperature for 12 hours to remove the excess metal cobalt on the surface, and then the diamond polycrystalline block was placed in a mixed acid (nitric acid and sulfuric acid) and heated at about 250°C for 60 hours to remove the residual metal and graphite. The sintered sample was in the form of a sheet. After multiple ultrasonic treatments with anhydrous ethanol and deionized water, a black, shiny and insulating DD-bonded diamond polycrystalline block was obtained. Figure 3 shown.
[0065] Figure 4This is a scan of the diamond particles prepared in Example 8. It can be seen from the scan that diamond particles with clear interfaces are exposed after acid treatment; large particles are connected together by small particles; the gaps are magnified and observed, and secondary growth grains are found. The secondary grains can form a heat conduction path for the pure diamond contact end, thereby improving thermal conductivity.
[0066] The test shows that its thermal conductivity reaches 1063W / (m·K).
[0067] Example 9
[0068] 300μm diamond particles were acid-washed and rinsed with deionized water and stored in a drying oven; the dried diamond particles were placed in the assembly, cobalt sheets were placed on the top and bottom surfaces of the diamond particles, the mass ratio of diamond particles to cobalt sheets was 1:0.25, and the assembly components were isolated with a boron nitride cup, that is, the sample was placed in the boron nitride cup. After assembly, it was placed in a six-sided top press device, and high-temperature and high-pressure sintering began in an air environment. The sintering pressure was set to 5.7GPa, and the six-sided hammer began to apply pressure at a rate of 7MPa / min to 3.5GPa, and then began to heat to 1390℃ at a rate of 200℃ / min, and then the pressure was raised to 5.7GPa, and the temperature was kept for 10min, and the heating was stopped first and then the pressure was released, and the diamond polycrystalline block was taken out after the end. The sample was first placed in 6 mol / L dilute nitric acid at room temperature for 12 hours to remove the excess metal cobalt on the surface, and then the diamond polycrystalline block was placed in a mixed acid (nitric acid and sulfuric acid) and heated at about 250°C for 60 hours to remove the residual metal and graphite. The sintered sample was in the form of a sheet, and after multiple ultrasonic treatments in anhydrous ethanol and deionized water, a black surface, shiny and insulating DD-bonded diamond polycrystalline block was obtained.
[0069] The test shows that its thermal conductivity reaches 823W / (m·K).
[0070] Example 10
[0071] 500μm diamond particles were acid-washed and rinsed with deionized water and stored in a drying oven; the dried diamond particles were placed in the assembly, cobalt sheets were placed on the top and bottom surfaces of the diamond particles, the mass ratio of diamond particles to cobalt sheets was 1:0.25, and the assembly components were isolated with a boron nitride cup, that is, the sample was placed in a boron nitride cup. After assembly, it was placed in a six-sided top press device, and high-temperature and high-pressure sintering began in an air environment. The sintering pressure was set to 5.7GPa, and the six-sided hammer began to apply pressure at a rate of 7MPa / min to 3.5GPa, and then began to heat to 1390℃ at a rate of 200℃ / min, and then the pressure was raised to 5.7GPa, and the temperature was kept for 10min, and the heating was stopped first and then the pressure was released, and the diamond polycrystalline block was taken out after the end. The sample was first placed in 6 mol / L dilute nitric acid at room temperature for 12 hours to remove the excess metal cobalt on the surface, and then the diamond polycrystalline block was placed in a mixed acid (nitric acid and sulfuric acid) and heated at about 250°C for 60 hours to remove the residual metal and graphite. The sintered sample was in the form of a sheet, and after multiple ultrasonic treatments in anhydrous ethanol and deionized water, a black surface, shiny and insulating DD-bonded diamond polycrystalline block was obtained.
[0072] The test shows that its thermal conductivity reaches 890W / (m·K).
[0073] Embodiment 11
[0074] 900μm diamond particles were acid-washed and rinsed with deionized water and stored in a drying oven; the dried diamond particles were placed in the assembly, cobalt sheets were placed on the top and bottom surfaces of the diamond particles, the mass ratio of diamond particles to cobalt sheets was 1:0.3, and the assembly components were isolated with a boron nitride cup, that is, the sample was placed in a boron nitride cup. After assembly, it was placed in a six-sided top press device, and high-temperature and high-pressure sintering began in an air environment. The sintering pressure was set to 6.0GPa, and the pressure was applied to 3.8GPa at a rate of 2MPa / min by a six-sided hammer, and then heated to 1420℃ at a rate of 200℃ / min, and then the pressure was raised to 5.9GPa, and the temperature was kept for 60min. The heating was stopped first and then the pressure was released. After the end, the diamond polycrystalline block was taken out. The sample was first placed in 6 mol / L dilute nitric acid at room temperature for 12 hours to remove the excess metal cobalt on the surface, and then the diamond polycrystalline block was placed in a mixed acid (nitric acid and sulfuric acid) and heated at about 240°C for 62 hours to remove the residual metal and graphite. The sintered sample was in the form of a sheet, and after multiple ultrasonic treatments in anhydrous ethanol and deionized water, a black surface, shiny and insulating DD-bonded diamond polycrystalline block was obtained.
[0075] The test shows that its thermal conductivity reaches 863W / (m·K).
[0076] Example 12
[0077] 500μm diamond particles were acid-washed and rinsed with deionized water and stored in a drying oven; the dried diamond particles were placed in the assembly, cobalt sheets were placed on the top and bottom surfaces of the diamond particles, the mass ratio of diamond particles to cobalt sheets was 1:0.28, and the assembly components were isolated with a boron nitride cup, that is, the sample was placed in the boron nitride cup. After assembly, it was placed in a six-sided top press equipment, and high-temperature and high-pressure sintering began in an air environment. The sintering pressure was set to 6.0GPa, and the six-sided hammer began to apply pressure at a rate of 4MPa / min to 3.6GPa, and then began to heat to 1420℃ at a rate of 200℃ / min, and then the pressure was raised to 6.0GPa, and the temperature was kept for 30min. The heating was stopped first and then the pressure was released. After the end, the diamond polycrystalline block was taken out. The sample was first placed in 6 mol / L dilute nitric acid at room temperature for 12 hours to remove the excess metal cobalt on the surface, and then the diamond polycrystalline block was placed in a mixed acid (nitric acid and sulfuric acid) and heated at about 230°C for 61 hours to remove the residual metal and graphite. The sintered sample was in the form of a sheet, and after multiple ultrasonic treatments in anhydrous ethanol and deionized water, a black surface, shiny and insulating DD-bonded diamond polycrystalline block was obtained.
[0078] The test shows that its thermal conductivity reaches 943W / (m·K).
[0079] Comparative Example 1
[0080] 500μm diamond particles were acid-washed and rinsed with deionized water and stored in a drying oven; the dried diamond particles were placed in the assembly, cobalt sheets were placed on the top and bottom surfaces of the diamond particles, the mass ratio of diamond particles to cobalt sheets was 1:0.25, and the assembly components were isolated with a boron nitride cup, that is, the sample was placed in a boron nitride cup. After assembly, it was placed in a six-sided top press device, and high-temperature and high-pressure sintering began in an air environment. The sintering pressure was set to 5.38GPa, and the six-sided hammer began to apply pressure at a rate of 7MPa / min to 3.5GPa, and then began to heat to 1310℃ at a rate of 200℃ / min, and then the pressure was raised to 5.38GPa, and the temperature was kept for 15min. The heating was stopped first and then the pressure was released. After the end, the diamond polycrystalline block was taken out. The sample was first placed in 6 mol / L dilute nitric acid at room temperature for 12 hours to remove the excess metal cobalt on the surface, and then the diamond polycrystalline block was placed in a mixed acid (nitric acid and sulfuric acid) and heated at about 250°C for 60 hours to remove the residual metal and graphite. The sintered sample was in the form of a sheet, and after multiple ultrasonic treatments in anhydrous ethanol and deionized water, a black surface, shiny and insulating DD-bonded diamond polycrystalline block was obtained.
[0081] The test shows that its thermal conductivity reaches 750W / (m·K).
[0082] Comparative Example 2
[0083] 200μm diamond particles were acid-washed and rinsed with deionized water and stored in a drying oven; the dried diamond particles were placed in the assembly, cobalt sheets were placed on the top and bottom surfaces of the diamond particles, the mass ratio of diamond particles to cobalt sheets was 1:0.25, and the assembly components were isolated with a boron nitride cup, that is, the sample was placed in the boron nitride cup. After assembly, it was placed in a six-sided top press equipment, and high-temperature and high-pressure sintering began in an air environment. The sintering pressure was set to 5.38GPa, and the six-sided hammer began to apply pressure at a rate of 7MPa / min to 3.5GPa, and then began to heat to 1310℃ at a rate of 200℃ / min, and then the pressure was raised to 5.38GPa, and the temperature was kept for 15min. The heating was stopped first and then the pressure was released. After the end, the diamond polycrystalline block was taken out. The sample was first placed in 6 mol / L dilute nitric acid at room temperature for 12 hours to remove the excess metal cobalt on the surface, and then the diamond polycrystalline block was placed in a mixed acid (nitric acid and sulfuric acid) and heated at about 250°C for 60 hours to remove the residual metal and graphite. The sintered sample was in the form of a sheet, and after multiple ultrasonic treatments in anhydrous ethanol and deionized water, a black surface, shiny and insulating DD-bonded diamond polycrystalline block was obtained.
[0084] The test shows that its thermal conductivity reaches 700W / (m·K).
[0085] Comparative Example 3
[0086] 200μm diamond particles were acid-washed and rinsed with deionized water and stored in a drying oven; the dried diamond particles were placed in the assembly, cobalt sheets were placed on the top and bottom surfaces of the diamond particles, the mass ratio of diamond particles to cobalt sheets was 1:0.25, and the assembly components were isolated with a boron nitride cup, that is, the sample was placed in a boron nitride cup. After assembly, it was placed in a six-sided top press device, and high-temperature and high-pressure sintering began in an air environment. The sintering pressure was set to 5GPa, and the pressure was applied at a rate of 7MPa / min to 3.5GPa by a six-sided hammer, and then heated to 1240℃ at a rate of 200℃ / min, and then the pressure was raised to 5GPa, and the temperature was kept for 10min. The heating was stopped first and then the pressure was released. After the end, the diamond polycrystalline block was taken out. The sample was first placed in 6 mol / L dilute nitric acid at room temperature for 12 hours to remove the excess metal cobalt on the surface, and then the diamond polycrystalline block was placed in a mixed acid (nitric acid and sulfuric acid) and heated at about 250°C for 60 hours to remove the residual metal and graphite. The sintered sample was in the form of a sheet, and after multiple ultrasonic treatments in anhydrous ethanol and deionized water, a black surface, shiny and insulating DD-bonded diamond polycrystalline block was obtained.
[0087] The test shows that its thermal conductivity reaches 382W / (m·K).
[0088] Comparative Example 4
[0089] 100μm diamond particles were acid-washed and rinsed with deionized water and stored in a drying oven; the dried diamond particles were placed in the assembly, cobalt sheets were placed on the top and bottom surfaces of the diamond particles, the mass ratio of diamond particles to cobalt sheets was 1:0.25, and the assembly components were isolated with a boron nitride cup, that is, the sample was placed in a boron nitride cup. After assembly, it was placed in a six-sided top press device, and high-temperature and high-pressure sintering began in an air environment. The sintering pressure was set to 5GPa, and the pressure was applied at a rate of 7MPa / min to 3.5GPa by a six-sided hammer, and then heated to 1200℃ at a rate of 200℃ / min, and then the pressure was raised to 5.7GPa, and the temperature was kept for 10min. The heating was stopped first and then the pressure was released. After the end, the diamond polycrystalline block was taken out. The sample was first placed in 6 mol / L dilute nitric acid at room temperature for 12 hours to remove excess metal cobalt on the surface. The diamond polycrystalline block was then placed in a mixed acid (nitric acid and sulfuric acid) and heated at 250°C for 2 hours. It was found that the diamond particles were loose and the diamond particles did not combine successfully.
[0090] Comparative Example 5
[0091] 200μm diamond particles were acid-washed and rinsed with deionized water and stored in a drying oven; the dried diamond particles were placed in the assembly, cobalt sheets were placed on the top and bottom surfaces of the diamond particles, the mass ratio of diamond particles to cobalt sheets was 1:0.25, and the assembly components were isolated with a boron nitride cup, that is, the sample was placed in a boron nitride cup. After assembly, it was placed in a six-sided top press device, and high-temperature and high-pressure sintering was started in an air environment. The sintering pressure was set to 5GPa, and the pressure was applied at a rate of 7MPa / min to 3.5GPa by a six-sided hammer, and then heated to 1300℃ at a rate of 200℃ / min, and then the pressure was raised to 5.7GPa, and the temperature was kept for 20min. The heating was stopped first and then the pressure was released. After the end, the diamond polycrystalline block was taken out. The sample was first placed in 6 mol / L dilute nitric acid at room temperature for 12 hours to remove excess metal cobalt on the surface, and then the diamond polycrystalline block was placed in a mixed acid (nitric acid and sulfuric acid) and heated at about 250°C for 60 hours to remove residual metal and graphite. When the sample was taken out, it was found that the diamond particles in the center of the sample had not been successfully aggregated and were severely graphitized.
[0092] In the “Study on High-Pressure Synthesis of DD-bonded Diamond Polycrystals” published in the Journal of High Pressure Physics, Hong Shiming et al. used diamonds with a particle size of 7μm to 80μm for preparation, which limited the source of raw materials. This is also the case with the prior art recorded in the background technology of the present invention, which uses fine-grained diamonds for preparation, and some samples in the article were vacuum-treated, that is, they need to be prepared in a vacuum system, and the environmental requirements during preparation are high. In addition, the article did not conduct relevant tests on the thermal properties of the prepared samples. In the past research history, research related to the thermal conductivity of diamond polycrystals has not received sufficient attention. In addition, the diamond polycrystals used have always been fine-grained. Considering all aspects comprehensively, the thermal conductivity of such fine-grained diamond polycrystals is estimated to be at a low level. However, the present invention uses low-cost abrasive-grade diamond as raw material for sintering, and the diamond polycrystals prepared by high temperature and high pressure method have excellent thermal conductivity.
[0093] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0094] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a self-supporting diamond polycrystalline material, characterized in that: The following steps are involved: Using cobalt as a binder, diamond particles of 50 μm to 900 μm are sintered at 1390° C. to 1420° C. and 5.7 GPa to 6.0 GPa. During the sintering process, secondary growth occurs between the diamond particles. After sintering, impurities are removed to obtain a self-supporting diamond polycrystalline material.
2. The method for preparing a self-supporting diamond polycrystalline material according to claim 1, characterized in that: The particle size of the diamond particles is 200 μm to 900 μm.
3. The method for preparing a self-supporting diamond polycrystalline material according to claim 1, characterized in that: The particle size of the diamond particles is 500 μm.
4. The method for preparing a self-supporting diamond polycrystalline material according to claim 1, characterized in that: The mass ratio of diamond particles to cobalt is 1:0.25-0.
3.
5. The method for preparing a self-supporting diamond polycrystalline material according to claim 1, characterized in that: The sintering method is as follows: when the pressure reaches 3.5 GPa to 3.8 GPa, heating to 1390° C. to 1420° C. is started, and at the same time, the pressure is increased to 5.7 GPa to 6.0 GPa for sintering.
6. The method for preparing a self-supporting diamond polycrystalline material according to claim 1, characterized in that: The sintering time is 10min-60min.
7. The method for preparing a self-supporting diamond polycrystalline material according to claim 1, characterized in that: The method for removing impurities is: placing the sintered sample in nitric acid to remove excess cobalt, and then placing it in a mixed acid and heating it at 230°C to 250°C to remove residual metal and graphite.
8. The method for preparing a self-supporting diamond polycrystalline material according to claim 7, characterized in that: The heating time is 60h~62h.
9. A self-supporting diamond polycrystalline material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the self-supporting diamond polycrystalline material according to claim 9 in preparing a thermal conductive material.
Citation Information
Cited By
Lightweight nanopore diamond and preparation method thereof
CN120423542A